Economic and Environmental Benefits of Energy Recovery from Municipal Solid Waste in Phnom Penh Municipality, Cambodia - Dek Vimean Pheakdey; Nguyen Van Quan; Tran Dang Xuan (Energies, 2023)
This study assessed the energy potential, economic feasibility, and environmental performance of landfill gas (LFG) recovery, incineration, and anaerobic digestion (AD) technologies for Phnom Penh municipality in Cambodia, from 2023 to 2042. The economic analysis utilized the levelized cost of electricity (LCOE), payback period (PBP), and net present value (NPV) to evaluate the feasibility of each technology. Additionally, environmental performance was assessed following the IPCC 2006 guidelines. The results indicate that incineration produced the highest energy output, ranging from 793.13 to 1625.81 GWh/year, while the LFG and AD technologies yielded equivalent amounts of 115.44–271.81 GWh/year and 162.59–333.29 GWh/year, respectively. The economic analysis revealed an average LCOE of 0.070 USD/kWh for LFG, 0.053 USD/kWh for incineration, and 0.093 USD/kWh for AD. Incineration and LFG recovery were found to be economically feasible, with positive NPVs and a potential for profit within 8.36 years for incineration and 7.13 years for LFG. In contrast, AD technology had a negative NPV and required over 20 years to generate a return on investment. However, AD was the most promising technology regarding environmental performance, saving approximately 133,784 tCO2-eq/year. This study provides valuable technical information for policymakers, development partners, and potential investors to use in order to optimize waste-to-energy investment in Cambodia.